Phase transition in Ferromagnetic Lattice models on a Cayley tree with non-uniform external magnetic fields - Ganikhodjaev, Nasir (2011)
In this article we study the phase transition phenomenon for the Ising and Potts models under the action of a non-uniform external magnetic field hx, x V, where V is the set of vertices of the Cayley tree. We show that both models on the Cayley tree with –J < inf {hx: x V} < sup{ hx: x V} < J, have a first-order phase transition